Manajemen Sumber Daya Manusia (MSDM) Pendidik dan Tenaga Kependidikan Terhadap Peningkatan Kualitas Proses Belajar Mengajar Pada Era Digital di SMK Negeri 1 Keruak: Human Resource Management (HRM) of Educators and Education Personnel on Improving the Quality of the Teaching and Learning Process in the Digital Era at SMK Negeri 1 Keruak - Muhamad Zaril Gapari (Al-Faiza : Journal of Islamic Education Studies, 2025)
Human Resources of Educators and Education Personnel have a very important role in improving the quality of the teaching and learning process, especially in the current digital era. The objectives of this study are: 1) to determine the factors that influence the effectiveness of human resource management, 2) to determine human resource management strategies, 3) to determine the challenges and solutions in managing human resources of educators and education personnel to face changes and demands of digital era learning. The type of research used is qualitative descriptive research, data was obtained by conducting observations, interviews, and documentation. The validity of the researcher's data used triangulation techniques. Data analysis was carried out in four stages, namely: data collection, data reduction, data presentation, and drawing conclusions. The results of the study show: 1. Human resource management is implemented through digital competency-based teacher and education personnel needs planning, continuous professional training and development, and technology-based performance evaluation. 2. Strategies implemented to improve the quality of learning include: a). improving teacher competency through regular digital training, b). optimal utilization of digital learning platforms by teachers and education personnel, c). provision of supporting facilities such as internet networks and ICT devices, and d) strengthening a collaborative culture among educators in the development of digital learning media and methods. Evaluation is conducted in a structured and continuous manner to ensure the effectiveness of HR management implementation in the digital era.